Strategi Kebijakan Pengelolaan Berkelanjutan Kawasan Pesisir di Wilayah Pesisir Kota Makassar: Sustainable Management Policy Strategy of Coastal Area on Makassar Coastal Territorial Water - Ridwan Bohari (Media Konservasi, 2009)
One of important coastal area is region of Makassar town coastal area. The area represented coastal region that has various exploiting characteristic and interconnected one another. The main purpose of this researcah is to analyze the sustainable management policy strategy of coastal area. To reach the especial target, hence there are some activity which require to be conducted as special target that are (1) identyfying determinant in future (2) determining strategic target and importance of main stakholder; and (3) defining and describe of evolution possibility of future. The prospektif analyse conducted in order to yielding sustainable regional development scenario of coastal area in Makassar town for future, with determining key factor that having an effect on to system performance. From various possibilities that could happen, is formulated three regional development scenario of Makassar town coastal are to come, that are: (1) Conservative-Pessimistic by conducting to repair of main key factor only, (2) , Moderate - Optimistic by conducting repair about 50% of main key attribute (factor), and (3) Progressive - Optimistic by conducting repair to entire key attribute (factor) to increase of sustainable status forwards )long-period), scenario which require to be conducted to increasae regional sustainable development status of coastal region of Makassar town is Progresive- Optimistic scenario by conducting repair by totally to all sensitive attribute so that all dimension become sustainable for coastal region development. Keywords: coastal region, sustainability, policy